30 Assessment and management of acute alcohol withdrawal – an audit. (5th April 2017) - Byrne, J; Aziz, R; Fitzgerald, SJ; O'Leary, C; O'Regan, P; Donnellan, C
Abstract : Background: 40% of individuals will develop an acute withdrawal syndrome upon stopping or significantly curtailing alcohol intake. A detailed alcohol history can be a useful aid in indentifying those at risk and avoiding adverse consequences of withdrawal. Aim: The aims of this audit were to quantify the proportion of acute admissions where an alcohol history is taken, assess the proportion of patients who were prescribed chlordiazepoxide and the doses used, assess the proportion of patients who were prescribed parenteral multivitamins, and the dose and duration of same. Method: Consecutive case series of 49 patients admitted to STGH from January-December 2016 with HIPE coding of "alcohol dependence with acute withdrawal". The Guys and St. Thomas' NHS Foundation Trust Clinical Guidelines on the detection of alcohol misusers attending hospital were used as reference standard. Results: In 82% (40/49 patients) a clear alcohol history was documented. For 62% of patients (30/49), the number of units of alcohol/week consumed was clearly documented. Median units/week was 50, with a range of 0-250. In 47% (23/49) of cases, a relevant neurological exam was documented in the admission note. Chlordiazepoxide was perscribed in 47% (23/49) of patients, with a median dose of 30 mg tds. Parenteral multivitamins were prescribed in 61% (30/49), for a median duration of 3 days. Conclusions: There exists a significant discrepancy between those identified at risk of acute alcohol withdrawal, and those for whom appropriate treatment is prescribed. Reasons include embedded prescribing practices, time constraints in ED, and uncertainty around appropriate dosing of chlordiazepoxide and parenteral multivitamins.